Assessing Awareness Level of Halal Cosmetics among Muslim Males in Malaysia: An Empirical Study - Nur Ilma Ambo; Ana Shakirah Md Shapir (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2021)
In the Proceeding of International Conference on Education Research (InCER 2020), Ambo & Md Sapir (2020) presented four items that measure halal cosmetic awareness among Muslim males. Unfortunately, INCER 2020's audience thought that the categorisation of respondents based on their marital status did not translate to good results since only ten respondents represented married males in the study out of 86. This paper aims to respond to the feedback given by the INCER 2020's audience by re-analysing the level of halal cosmetic awareness of 86 Muslim males in Malaysia in terms of age, educational level, Islamic background, and marital status, and employing Chi-Square and Independence Sample T-Test. The findings showed that Muslim males with Islamic backgrounds obtain a high level of halal cosmetic awareness than their non-Islamic counterparts. The study findings indicate that presenting conceptual ideas at the Conference helped us receive constructive feedback to improve our research work